2007
DOI: 10.1159/000104718
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome in Hemodialysis Patients: Association with Calcium Antagonists

Abstract: Uremia-related restless legs syndrome (RLS) is a known form of secondary RLS. This cross-sectional survey included patients (n = 82) on stable hemodialysis (HD; >3 months, Kt/V >1.2) who were iron-replete, free of neurodegenerative or psychiatric disorders, severe polyneuropathy and radiculopathy, not exposed to antipsychotics/antidepressants, and not severely anemic. Forty-nine (60%) were RLS ‘positive’, and 25 (31%) had severe/very severe symptoms (International Restless Legs Syndrome Study Group criteria). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
2
7
1
2
Order By: Relevance
“…Heterogeneity is also present in the studies that investigated RLS prevalence in patients with MS, which could explain diff erences in the estimated prevalence among the studies 11 . Pooled analysis performed in the meta-analysis by Schürsk and Bussfeld 11 indicates that MS is associated with a fourfold increase in the odds for RLS compared with people without MS. Th is is in concordance with our survey, since the estimated prevalence of the idiopathic form of RLS in Croatia is 9.5% 16 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Heterogeneity is also present in the studies that investigated RLS prevalence in patients with MS, which could explain diff erences in the estimated prevalence among the studies 11 . Pooled analysis performed in the meta-analysis by Schürsk and Bussfeld 11 indicates that MS is associated with a fourfold increase in the odds for RLS compared with people without MS. Th is is in concordance with our survey, since the estimated prevalence of the idiopathic form of RLS in Croatia is 9.5% 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Although the true reason for this is not known, cervical cord damage was found to be associated with a higher prevalence of RLS in MS patients 15 . Th e prevalence of idiopathic RLS in Croatia is 9.5% 16 . In this study, we investigated RLS prevalence in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies had provided evidence that longer history of dialysis was a risk factor of RLS. 28,33,34 One suggested that RLS was caused by the accumulation of a middle molecule in dialysis-related amyloid, which was similar to the accumulation of b 2 -microglobulin. 11 However, longer duration of dialysis was reported not to affect the risk in another three studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca yaşla birlikte sıklığı artmaktadır. Yapılan çalışmalarda HD hastalarında HBS sıklığı, Amerika'da (%20,8), Hırvatistan'da (%60) olarak saptanmıştır [20,21]. Türkiye'de Çölbay ve arkadaşlarının yaptığı 95 hemodiyaliz hastasının alındığı çalışmada HBS sıklığı %45,3 oranda (43 hastada) tespit edilmiştir.…”
Section: Discussionunclassified
“…HD hastalarında ise yaşın HBS gelişimi açısından bir risk faktörü olmadığına dair yayınlar bulunmaktadır [21]. Dikkat edilmesi gereken konulardan biri de diyaliz hastalarında başta üremik nöropati, periferik vasküler hastalıklar ve diabetik nöropati olmak üzere HBS ile karışabilecek pek çok sorunun beraber bulunmasıdır.…”
Section: Discussionunclassified